Laparoscopic Colorectal Cancer Surgery : Operative Procedures Based on the Embryological Anatomy of the Fascial Composition - Mike, Makio (Springer Singapore : Imprint: Springer, 2017)
This unique guide describes colorectal surgery procedures using medical terminology and anatomical terms originating from embryology. In the last decade, laparoscopic procedures in gastrointestinal surgery have been enhanced and their safety has significantly improved. With the number of cases of colorectal cancer surgery increasing and laparoscopic surgery no longer considered a specialized surgery, the recognition of the correct anatomy is vital in these procedures. Unfortunately, however, the understanding of clinical anatomy is frequently separate from that of basic surgical concepts. Initially, the dissecting layer should be presumed to derive from the fascial anatomy based on embryological recognition. Furthermore, the techniques currently being used by surgeons should be described in sufficient detail and the appropriate anatomical terms should always be used. In view of this, this valuable monograph benefits gastrointestinal surgeons and general surgeons who are involved in the treatment of colorectal cancer.